Effects of ultrasound-guided stellate ganglion block on intrapulmonary shunt and oxygenation in patients with single-lung ventilation - Zhu, Guoshao; Su, Changsheng; Kang, Zhenming; Zeng, Jingyang; Li, Shunyuan (Frontiers in Surgery, 2024)
BackgroundSingle-lung ventilation (SLV) is a widely used procedure in thoracic surgery; however, it can lead to hypoxemia, which is attributed to intrapulmonary shunt and hypoxic pulmonary vasoconstriction. Stellate ganglion blockade (SGB) has shown protective effects during SLV in various pulmonary conditions. The objective of the study was to assess the clinical utility of ultrasound-guided SGB in patients undergoing thoracoscopic pulmonary lobectomy through a prospective clinical trial.MethodsThis prospective randomized controlled double-blind trial included 116 patients who underwent SLV. After exclusion, 88 patients were randomly assigned to either the SGB group (n = 40) or control group (n = 39), with the latter receiving no SGB. Hemodynamics using oxygenation index (OI) and the pulmonary shunt fraction (Qs/Qt), respiratory mechanics using dynamic lung compliance (Cdyn) and mean airway pressure (Pmean), and levels of pro-inflammatory factors (IL-6 and IL-8) were assessed as clinical outcomes after surgery.ResultsSLV induced upregulation of Pmean, Qs/Qt, and levels of IL-6 and IL-8 and downregulation of Cdyn and OI. Compared to the control group, the SGB group demonstrated significantly decreased Pmean, Qs/Qt, IL-6, and IL-8 and increased Cdyn and OI, suggesting the protective effects of SGB in patients who received SLV.ConclusionsUltrasound-guided SGB improves respiratory mechanics, hemodynamics, and inflammatory responses during SLV. Our findings suggest a protective role of SGB in reducing complications associated with SLV.Clinical Trial RegistrationThe study was registered in the Chinese Clinical Trial Registry (#ChiCTR2200063210).